2020
DOI: 10.1111/1750-3841.15175
|View full text |Cite
|
Sign up to set email alerts
|

Consumer acceptability in the USA, Mexico, and Spain of chocolate chip cookies made with partial insect powder replacement

Abstract: In the last decade, consumer perception of protein as an important nutrient has increased exponentially and focused on alternative sources such as plant‐ or insect‐based protein and microalgae. However, many consumers indicate that they do not consider insect ingredients, a potential source of high quality protein, to be a good choice in food products. But is it because of the sensory aspects? This consumer study was conducted in the United States of America, Mexico, and Spain to compare acceptability of a fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…On the contrary, males had a similar frequency of consumption intent across all treatments. Females may have had lower thresholds for the detection or recognition of ECP in the brownie formulation than males [ 47 ] or male consumers while recognizing a difference in the sensory properties of treatments with ECP, but still presented the same willingness to consume them as for those without ECP because males had higher blind acceptability for ECP than women [ 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, males had a similar frequency of consumption intent across all treatments. Females may have had lower thresholds for the detection or recognition of ECP in the brownie formulation than males [ 47 ] or male consumers while recognizing a difference in the sensory properties of treatments with ECP, but still presented the same willingness to consume them as for those without ECP because males had higher blind acceptability for ECP than women [ 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, males had a similar frequency of consumption intent across all treatments. Females may have had lower thresholds for the detection or recognition of ECP in the brownie formulation than males [47] or male consumers while recognizing a difference in the sensory properties of treatments with ECP, but still presented the same willingness to consume them as for those without ECP because males had higher blind acceptability for ECP than women [48][49][50]. Regarding purchase intent, females exhibited higher (p < 0.05) frequency for treatments without ECP (CBWO− and CBWO+), but the treatment containing ECP and the informed condition (CBW+) achieved similar purchase intent to CBWO−, demonstrating a positive effect of the informed condition (purchase intent increased from 27% for CBW− to 38% for CBW+; Figure 5).…”
Section: Consumption and Purchase Intent Segmented By Gendermentioning
confidence: 99%
“…Further research by Caparros Megido et al (2016) assessed sensory liking of mealworm burgers with Belgium consumers and found that consumers rated the taste and appearance of the insect burger between a beef burger and a lentil burger. Cookies containing 15% cricket powder were also found to be acceptable in a sensory evaluation by consumers from the United States, Mexico, and Spain (Castro Delgado et al, 2020). In fact, overall liking for cookies containing 15% cricket powder were preferred to the control amongst consumers from Mexico and Spain.…”
Section: Discussionmentioning
confidence: 99%
“…Lombardi et al (2019) found that younger people were more willing to try new products like insects, while other researchers found no significant influence of age on acceptance of insects (Hartmann et al, 2015; Jensen & Lieberoth, 2019; La Barbera et al, 2017; Lammers et al, 2019; Piha et al, 2018; Tan et al, 2016; Woolf et al, 2019). Further, sensory evaluation of chocolate chip cookies in the United States, Mexico, and Spain found that overall liking by gender and age varied based on the country (Castro Delgado et al, 2020). Thus, while some research suggests that younger males are the most likely to consume insects, the evidence is inconsistent and suggests that factors other than age and gender may be more influential on willingness to consume insects.…”
Section: Introductionmentioning
confidence: 99%
“…Before experiencing the taste of cricket powder, Canadian consumers thought that consumption was undesirable, but their attitude changed after having consumed the powder and they were then willing to buy it [ 186 ]. In the USA, Mexico and Spain, replacing wheat flour with 15% and 30% of cricket ( A. domesticus ) powder in chocolate chip cookies was evaluated [ 187 ]. No difference between 15% and 30% was noted by USA consumers whilst Mexican and Spanish consumers liked the 15% sample significantly more than the control and 30% sample.…”
Section: Impact Of Insect Quality On Consumers’ Preference and Acceptabilitymentioning
confidence: 99%